The history of the Moravian Church rooting in Unitas Fratrum or the Unity of the Brethren (1457-2017) based on the description of the two settlements of Christiansfeld and Sarepta - Christensen Carsten Sander (Studia Humanitatis, 2017)
The article deals with the history and the problems of the Moravian Church rooting back to the Unity of the Brethren or Unitas Fratrum, a Czech Protestant denomination established around the minister and philosopher Jan Hus in 1415 in the Kingdom of Bohemia. The Moravian Church is thereby one of the oldest Protestant denominations in the world. With its heritage back to Jan Hus and the Bohemian Reformation (1415-1620) the Moravian Church was a precursor to the Martin Luther’s Reformation that took place around 1517. Around 1722 in Herrnhut the Moravian Church experienced a renaissance with the Saxonian count Nicolaus von Zinzendorf as its protector. A 500 years anniversary celebrated throughout the Protestant countries in 2017. The history of the Moravian Church based on the description of two out of the 27 existing settlements, Christiansfeld in the southern part of Denmark and Sarepta in the Volgograd area of Russia, is very important to understand the Reformation in 1500s.